Influência da lista vermelha e de características das espécies no esforço em pesquisa de anuros do Brasil - Monteiro, Vitor Guimarães (2022)
The red list of endangered species is an important tool that presents data on the threat of extinction and also population trends for several taxa. Therefore, the red list has as one of its functions, to direct research efforts to those species that are threatened with extinction and, therefore, require greater attention in order to maintain biodiversity. One of the objectives of this study was to investigate whether the red list is a good guide for the research effort on endemic endangered amphibians of Brazil. Another objective of the work was to verify if factors such as the average body size of a species, the range, the year of formal description or the biome influence the total number of articles that endemic amphibian species have. Through database research (Web of Science and Scopus), we found 1775 articles distributed among 17 families of endemic amphibian amphibians in Brazil. This work shows that only the threat category of each species does not explain the variation in the number of articles published for each species between the time of publication of this status and the year 2020. Species with larger body size, larger range and that have been described for a longer time showed a greater number of articles.